Red Blood Profile Of Monopterus Albus Preserved In Multitesely Systems With Different Stock Densities - Muhajir, Muhammad; Lukistyowati, Iesje; Syawal, Henni (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Biofloc is a technology using good bacteria to convert organic waste to be food source by fish in the form of floc. This research was carried out in April-May 2021 in the Hatchery and blood observations at the Fish Disease and Parasite Laboratory, Faculty of Fisheries and Marine, University of Riau. The purpose of this study was to determine the health status of eels from the profile of erythrocytes cells and the best stocking density of eels cultivated in biofloc system. While the benefits of this study can be applied to biofloc cultivation and apply it in the field. The research method used one-factor completely randomized design (CRD) with four treatment levels and three replications (12 experimental units) for 40 days . The optimal stocking density of eels in clean water is 6 fish for 10 liters. The treatments in this study were P1: stocking density of 10 fish/25 L, P2: stocking density of 20 fish/25 L, P3: stocking density of 30 fish/25 L, P4: stocking density of 40 fish/25 L. The results showed that the erythrocytes profile of eel with different stocking densities had a significant effect (P<0.05) and the best treatment P3 (30 fish/25 L) with total erythrocytes 2.88x106 cells/mm3, hematocrit level 31.66 %, hemoglobin levels 17.40 g/dL, blood glucose 46.33 g/dL, specific growth rate 93.3%, and feed efficiency 67.46%. Water quality in this study was in normal range, that is temperature 25.7-27.3 oC, pH 7.0-7.8, DO 6.4-8.0 mg/L, and NH3 0.0003-0.00038 mg/L.